2018
DOI: 10.1097/j.pain.0000000000001424
|View full text |Cite
|
Sign up to set email alerts
|

Facial muscle movements encoding pain—a systematic review

Abstract: Facial expressions of pain are not undefined grimaces but they convey specific information about the internal state of the individual in pain. With this systematic review we aim to answer the question of which facial movements are displayed most consistently during pain. We searched for studies that used the Facial Action Coding System (FACS) to analyze facial activity during pain in adults, and that report on distinct facial responses (Action Units, AUs). Twenty-seven studies using experimental pain and 10 cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
145
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 119 publications
(175 citation statements)
references
References 56 publications
10
145
2
2
Order By: Relevance
“…The five selected items on facial expressions are in agreement with previous findings on facial expressions of pain (Prkachin, ; Kunz, Meixner, & Lautenbacher, ). In a recent review article (Kunz et al, ), the findings of 37 studies on facial activity elicited during clinical and/or experimental pain were analysed, and it was found that a consistent subset of pain‐related facial responses emerged across studies: frowning, narrowing eyes, raising upper lip and opening mouth. These are the same facial responses that emerged as the best facial items in our PAIC15 item selection process.…”
Section: Discussionsupporting
confidence: 88%
“…The five selected items on facial expressions are in agreement with previous findings on facial expressions of pain (Prkachin, ; Kunz, Meixner, & Lautenbacher, ). In a recent review article (Kunz et al, ), the findings of 37 studies on facial activity elicited during clinical and/or experimental pain were analysed, and it was found that a consistent subset of pain‐related facial responses emerged across studies: frowning, narrowing eyes, raising upper lip and opening mouth. These are the same facial responses that emerged as the best facial items in our PAIC15 item selection process.…”
Section: Discussionsupporting
confidence: 88%
“…The item “pained expression”, for example, is originally defined as “facial expression of pain”, thus being subject to interpretation. We decided to consider a “pained expression” as present whenever at least two empirically derived pain‐specific facial movements occurred (Kunz & Lautenbacher, ; Kunz, Meixner, & Lautenbacher, ; Lautenbacher, Walz, & Kunz, ; Prkachin, ; Williams, ). Due to this operationalization the item ‘pained expression’ turned out to be particularly relevant in our further analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantage is the higher chance of certain distress behaviours occurring, making it more difficult for certain items to be confirmed as pain specific. This may in particular be true for “frowning” and “narrowing eyes”, facial movements that empirically were shown to be pain specific (Kunz & Lautenbacher, ; Kunz et al, ; Prkachin, ; Williams, ), but also occur if individuals are cognitively engaged.…”
Section: Discussionmentioning
confidence: 99%
“…However, data driven methods do not exist for the interpretation of such data in horses or other animals. We therefore explored statistical methods used in human FACS [17] and also developed novel statistical approaches to analyze the FACS data. This study describes for the first time the facial activities of horse in pain by use of EquiFACS.…”
Section: Discussionmentioning
confidence: 99%
“…While studies applying EquiFACS methods are few, research on human facial expressions of pain is mature and extensive. Kunz et al [17] presents a systematic review of studies on human facial expressions of pain and describe current approaches for the identification of action units associated with pain. The first criterion for defining an AU to be pain related is if it occurs frequently -forming more than 5% of total pain AU occurrences [18].…”
Section: Human Facs Interpretation (Hfi) Methodsmentioning
confidence: 99%